Book Catalog Application In Man 2 Bengkulu City Using The Levenstein Distance Algorithm - Reza Saputra; Sapri Sapri; Ricky Zulfiandry (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
MAN 2 Bengkulu City is one of the public madrasah aliyah schools in Bengkulu City. The school already has a library which is used as a medium for library members or users to search for books, read books, and borrow books. So far, the library at MAN 2 Bengkulu City is still conventional and has not used related applications in terms of searching book catalogs. Members/librarians come to the library and look directly at each shelf to pick up the desired book. In addition, the data processing of the book catalog has not utilized the office application package, all book data is processed using double polio paper that has been prepared. The book catalog application at MAN 2 Bengkulu City is an application that can be used to facilitate the library in managing book data, members, borrowing, and returning books and can print the output needed in archiving library data. The book catalog application at MAN 2 Bengkulu City has applied the Levenstein Distance Algorithm which is used to facilitate the search for books when the book borrowing process is carried out. The book catalog application at MAN 2 Bengkulu City was made using the Visual Basic programming language.